Plasma diagnostics for the low-pressure plasma polymerization process: A critical review - Thiry, Damien; Konstantinidis, Stephanos; Cornil, Jérôme; Snyders, Rony (Thin solid films, 2016)
Since the 1980s, functionalized plasma polymer films have attracted a considerable attention owing to their promising utilization in a wide range of modern applications. For such materials, controlling the chemistry of the coatings by a clever choice of the process parameters represents the main challenge. And yet, it became quickly obvious that in view of the complexity of the growth mechanism, fine control of the layers properties can only be reached by understanding at a fundamental level the mechanistic formation of the layers. In this context, a detailed comprehensive study of plasma chemistry is therefore of crucial importance as the numerous interlinked chemical reactions occurring in the discharge govern the film properties. In this paper, the most common plasma diagnostics methods employed in the context of plasma polymerization process, namely Mass Spectrometry, in-situ Fourier Transform Infrared Spectroscopy, Optical Emission Spectroscopy, Langmuir and Ionic probes are reviewed. After a light description of each technique, the main achievements for improving the mechanistic understanding of the layer formation are exposed. Moreover, the use of theoretical calculations based on Density Functional Theory (DFT) to support the understanding of the acquired data is highlighted. In view of the better control of the process allowed by the plasma phase investigation, some general conclusions and perspectives describing future developments in the field of plasma polymerization are finally discussed.